Aggregometry and thromboelastography to identify the timing to trach a COVID‐19 patient receiving both antiplatelet therapy and enoxaparin. Issue 3 (9th January 2021) - Tescione, Marco; Vadalà, Eugenio; Marano, Graziella; Bruni, Andrea; Garofalo, Eugenio; Lavalle, Ovidia; Longhini, Federico; Battaglia, Enzo; Polimeni, Nicola; Labate, Demetrio; Caracciolo, Sarah; Giordano, Francesco; et al.
Abstract: In COVID‐19 patients receiving enoxaparin and antiplatelets therapy, aggregometry and thromboelastography might be considered an adjunctive tool to identify the time to perform procedures at risk of bleeding, such as tracheostomy. Abstract : In COVID‐19 patients receiving enoxaparin and antiplatelets therapy, aggregometry and thromboelastography might be considered an adjunctive tool to identify the time to perform procedures at risk of bleeding, such as tracheostomy.